Forest Structure and Spesies Compotition in Taman Raya Bukit Soeharto, East Kalimantan - H R Syaukani; Cecep Kusmana; Hadi S Alikodra; Dudung Darusman; Kooswardhono Mudikdjo (Institut Pertanian Bogor (IPB University), 2005)
The species composition and forest structure of Taman Hutan Raya Bukit Soeharto - East Kalimantan were investigated using transect method through systematic sampling with random start design. During data collection,5 transects of 20 m width and 1 km length of each in Wanariset Semboja forest complex and 10 transects in Pusrehut UNMUL and Protection Forest areas were established. The study shows that species richness of trees in those three forest complexes are relatively similar, however, the regeneration stage in Pusrehut UNMUL forest complex is relatively higher than those in another two areas. Medang (Litsea firma), Acacia (Acacia sp.), and Mahang (Macaranga gigantea) are dominant tree species in Wanariset Semboja, Pusrehut UNMUL and Protection Forest areas, respectively. Mahang (M. gigantea) as pioneer species is also commonly dominated forest regeneration in Taman Hutan Raya Bukit Soeharto. Based on tree’s diameter distribution, those forests show balanced uneven-aged forests in which the large amount of trees are concentrated in the height class of 10 to 29 m. Species diversity of those forests are relatively high (H > 2.5) either for seedling, sapling, pole or tree growth stages, however, those forests show different plant communities (IS < 70 %).